Os saberes docentes dos profissionais que atuam nos laboratórios científicos quanto à formação inicial e continuada para utilização de atividades experimentais investigativas - Santos, Neila Andrade Tostes Lopez dos (2022)
The present research analyzed the entanglements of continuous teacher training in teachers' speeches about the Investigative Experimental Activities (AEI) and sought to reveal the conditions in which the teaching practice occurs in the Science Laboratories (LC) of three schools in the Campo Grande-MS Municipal Education Network. It means getting into the questions, the contexts of continuous teacher training, and also understanding the elements that compose it. The objective of this study was to investigate the teaching knowledge present in the speech of Science teachers who work in these laboratories regarding the continuous training for AEI. This reflection occurred in the area of Natural Sciences, especially regarding the contributions of the training to the pedagogical practice and how the AEI are developed. The research presents a methodology of qualitative approach with an exploratory design. Data were collected through a semi-structured interview and an online questionnaire, which were evaluated using content analysis, and lesson plans about the AEI, analyzed using the Diagnostic of Elements of Science Teaching by Investigation tool. The results showed that a major difficulty in using the laboratory is the lack of materials for the AEI because there are few of them, and most are donated or bought by the professionals themselves. The obstacle are the insufficient knowledge in designing investigation-oriented lessons and the time spent on the lesson in the LCs. The study showed that two teachers presented difficulties in several elements of teaching by investigation, that is, they had characteristics of a practical activity different from an experimental activity or were closer to a demonstration activity. We conclude that their statements bring Professional Knowledge and that Experimental Activities (AE) of demonstration, verification, and investigation was performed during initial training, but according to the analyses, we perceived some difficulties in the pedagogical application in relation to AEI. Initial training should bring more of the reality of schools to universities, taking the view of pedagogical AE, focused on teaching and learning in Science classes. Furthermore, we emphasize the importance of student participation in the investigation and the formulation of problems that are meaningful and related to their daily lives, enabling the expansion of scientific culture. The Disciplinary Knowledge is brought in when there are practical classes of AE and the elaboration of plans during the undergraduate courses. The Curricular Knowledge brings the organization of classes, which goes through the joint planning between the LC teacher and the regular teachers, based on materials available in the LC, and this is an interactive and productive work between them. Their Experiential Knowledge about the contributions of continuous teacher training pointed to the theoretical basis with ideas and suggestions on investigative practices in the teaching and learning processes, the exchange of experiences among teachers, and the promotion of the connection between theory and practice. As for the suggested changes in continuous teacher training, they are: bringing in the AEI with few resources and materials; introducing a remote advisory; creating an annual plan for continuous teacher training; and proposing a line of basic training that would evolve into an improvement of the professionals. As for the relevant characteristics of continuous teacher training, we can mention: it must contain theoretical bases; have well-prepared teachers; focus on the students; and the theories present in the continuous training can be developed according to the reality of the school community and bring suggestions, proposals, and ideas of educational practices. We conclude with the suggestion of producing an annual training plan and the evolution of continuous teacher training for an improvement that meets the teachers’ needs.